Combining µXANES and µXRD mapping to analyse the heterogeneity in calcium carbonate granules excreted by the earthworm Lumbricus terrestris. (1st January 2014) - Brinza, Loredana; Schofield, Paul F.; Hodson, Mark E.; Weller, Sophie; Ignatyev, Konstantin; Geraki, Kalotina; Quinn, Paul D.; Mosselmans, J. Frederick W.
<x xml:space="preserve">Abstract</x> The use of fluorescence full spectral micro‐X‐ray absorption near‐edge structure (µXANES) mapping is becoming more widespread in the hard energy regime. This experimental method using the Ca K‐edge combined with micro‐X‐ray diffraction (µXRD) mapping of the same sample has been enabled on beamline I18 at Diamond Light Source. This combined approach has been used to probe both long‐ and short‐range order in calcium carbonate granules produced by the earthworm Lumbricus terrestris. In granules produced by earthworms cultured in a control artificial soil, calcite and vaterite are observed in the granules. However, granules produced by earthworms cultivated in the same artificial soil amended with 500 p.p.m. Mg also contain an aragonite. The two techniques, µXRD and µXANES, probe different sample volumes but there is good agreement in the phase maps produced.